Study on Dendrobium officinale O-acetyl-glucomannan (Dendronan®): Part III–Immunomodulatory activity in vitro. Issue 2 (April 2015) - Cai, Hai-lan; Huang, Xiao-jun; Nie, Shao-ping; Xie, Ming-yong; Phillips, Glyn O.; Cui, Steve. W.
Abstract: Dendrobium officinale, ranked as the first of "Nine kinds of Chinese medicinal herbs", has been used for centuries to treat a variety of health problems. However, less is known about the active components which confer the therapeutic properties of D. officinale . In the present study, the effects of aqueous extract, crude polysaccharide and purified polysaccharide from the stems of D. officinale (Dendronan ® ) were examined on mouse macrophage line RAW 264.7 cells. Both aqueous extracts and polysaccharide are shown to be non-cytotoxic and can activate macrophages, resulting in enhancing phagocytic activity, up-regulating nitric oxide (NO), and influencing the cytokine production. Reverse transcription polymerase chain reaction (RT-PCR) showed that the increases in the secretion of NO, and cytokines are due to the increase in their mRNA expressions. Western immunoblotting revealed that Dendronan ® is able to up-regulate the expression of iNOS protein. Our data suggests a molecular basis to show that the active component of D. officinale is a purified polysaccharide, Dendronan ® . Graphical abstract: Highlights: Both aqueous extracts and polysaccharide from D. officinale are shown to be non-cytotoxic and can activate macrophages. The active component of D. officinale is a purified polysaccharide, Dendronan®, which can possibly be used for the modulation of immune response. The increases in NO and cytokine production is possibly due to an increase in relevant mRNA (iNOS, TNF-α, IL-6) and protein (iNOS) expression.